Optimizing precision in ICU arterial access: the impact of ultrasound-guided dynamic needle tip positioning - Chen, Xiuqin; Wu, Yongrui; Zhang, Li; Zhou, Ying; Fang, Hui (Frontiers in Medicine, 2025)
ObjectiveThis study aims to evaluate the efficacy of ultrasound-guided dynamic needle tip positioning (DNTP) in arterial puncture and catheterization among ICU patients.MethodsA cohort of 55 patients in shock, requiring arterial catheterization in the ICU from April 2020 to July 2024, was enrolled and randomly stratified into groups based on distinct ultrasound-guided puncture techniques. Of these, 27 patients who underwent the ultrasound-guided direct entry (UGDE) method were designated as the control group, while 28 patients who received arterial catheterization via the ultrasound-guided DNTP technique were assigned to the observation group. Comparative analyses were conducted on the first-attempt puncture success rate, first-attempt catheterization success rate, puncture duration, and incidence of puncture-related complications between the two groups.ResultsThe first-attempt puncture success rate did not significantly differ between the observation and control groups (P = 0.98). However, the observation group exhibited a higher first-attempt catheterization success rate (P = 0.049), an extended puncture duration (P < 0.001), and a reduced overall incidence of puncture-related complications (P = 0.049) in comparison to the control group.ConclusionThe application of ultrasound-guided DNTP methodology demonstrates statistically significant improvement in arterial catheterization procedural success rates concurrent with a marked reduction in iatrogenic vascular access complications.